Alex. Brown & Sons records - Alex. Brown & Sons.
Lettercopy and letterpress books, daybooks, cashbooks, ledgers, journals, salesbooks, wastebooks, accounts current, blotters, and other business records of the firm and its successor, subsidiary, and allied companies documenting its transition from a mercantile firm importing Irish linen to an international banking house with extensive import-export, shipbuilding, railroad, and public utility operations. The correspondence reflects social, political, and military events as well as financial and economic trends of the nineteenth century. Also includes records of Stewart Brown, Philadelphia, Pa., and Falls & Brown, Baltimore, Md. Other firms represented include the Baltimore and Ohio Railroad Company, Brown Brothers & Company, and Brown, Shipley & Co., its affiliate in Liverpool. Persons represented include the firm's founder, Alexander Brown (1764-1834); his descendants. Alexander Brown (1858-1949), George Brown (1787-1859), George Stewart Brown (1834-1890), James Brown (1791-1877). John A. Brown (1788-1872), and Sir William Brown (1784-1864); and his brother, Stewart Brown, and Stewart Brown's business partner, Moore Falls.
Containers 125, 198, and 242 available on microfilm only; originals retained by the firm.
Firm founded in 1800 in Baltimore, Md., that evolved from a mercantile business into an international banking house.
Collection material in English.
Finding aid available in the Library of Congress Manuscript Reading Room and at
Keywords: Brown, Alexander, -- 1764-1834.; Brown, Alexander, -- 1858-1949.; Brown, George, -- 1787-1859.; Brown, George Stewart, -- 1834-1890.; Brown, James, -- 1791-1877.; Brown, John A., -- 1788-1872.; Brown, Stewart, -- 1769-; Brown, William, -- Sir, -- 1784-1864.; Falls, Moore; Baltimore and Ohio Railroad Company; Brown Brothers & Company; Brown, Shipley & Co; Falls & Brown; Stewart Brown (Firm); Banks and banking -- Maryland -- Baltimore; Banks and banking, International; International finance; Linen industry -- Ireland; Merchants -- Maryland -- Baltimore; Merchants -- Pennsylvania -- Philadelphia; Public utilities; Shipbuilding; Trading companies; United States -- Economic conditions -- 19th century; United States -- History -- 19th century; United States -- Politics and government -- 19th century; United States -- Social life and customs -- 19th century